Sociodemographic and clinical characteristics and access to health care in patients with spinal muscular atrophy in Argentina - Vazquez, Gabriel Adolfo; Nasif, Salomé; Marciano, Sebastián; Pagotto, Vanina (Frontiers in Neurology, 2023)
The FAME registry gathers the majority of patients with SMA in Argentina. From it, the clinical, sociodemographic and access to treatment characteristics were analyzed in 322 patients (range 8 months-61 years) included from 2008 to 2021. Important data were obtained for the planning of medical care of these patients such as: similar distribution of patient care in public and private hospitals, time gap between onset of symptoms and diagnoses, low level of completion of SMN2 copy count, estimate of 16 new diagnoses per year between 2014 and 2018, and 68% of patient in specific pharmacological treatment.